Understanding where and why Senegalese adolescents and young adults access health information: A mixed methods study examining contextual and personal influences on health information seeking. (3rd April 2017) - Adams, Rachel M.; Riess, Helene; Massey, Philip M.; Gipson, Jessica D.; Prelip, Michael L.; Dieng, Thierno; Glik, Deborah C.
ABSTRACT: Background : Adolescent and young adult years are critical to the development of behaviors that influence health across the life course. To reveal which health communication channels should be used to effectively reach and influence younger populations in Senegal, we used a mixed methods approach to identify and interpret the multifaceted influences surrounding where and why this population accesses health information. Methods : We conducted 16 focus group discussions among adolescents and young adults in Senegal in September 2012. We then collected survey data from a larger, more diverse sample of Senegalese youth in October–November 2014. Results : Our results demonstrate that information sources vary by health topic, differential access, age, and other demographics. While there is a greater perception of credibility and usefulness in information received from health professionals, stigma remains a barrier for obtaining information about HIV/AIDS from health centers. Older youth are also less likely to seek health information from adults, which may be influenced by preferred use of information technologies, especially for information about taboo health topics. Conclusions : Our findings support multi-pronged, targeted approaches to health communication efforts. We recommend that doctors continue to provide actionable information about preventing or treating specific diseases, whereas teachers should educate youth about general health topics and health promotion behaviors. The results suggest that traditional mass media, such as radio and television, are the best communication channels for information about HIV and sexual/reproductive health, especially for older adolescents and young adults.